Expectations and deficiencies in educational visits to libraries and documentation centers: the lost opportunity - López-de-Quintana, Eugenio (Anuario ThinkEPI, 2014)
Visiting libraries and documentation departments is a common activity in information management teaching and training programs. However, these visits very often lack the necessary elements tomake them productive training experiences and not merely social activities. Prior preparation and identification of the students´ objectives and responsibilities, planning that ensures the visits are dynamic, andthe subsequent evaluation and sharing of the new ideas generated are some of the essential factors that foster reflection, critical thinking and participation.